Stress level among intensive care nurses in the municipality of Paraná (Brazil) - Kelly Cristina Inoue; Gelena Lucinéia Gomes da Silva Versa; Laura Misue Matsuda (Universidad de Antioquia, 2014)
Objective. To identify stress levels among intensive care nurses who work in the municipality of Western Paraná, Brazil. Methodology. This is a cross-sectional cohort study, carried out from May to July 2010, included 60 nurses from intensive care units (adult, pediatric, or neonatal) of five hospitals. All participants completed the Bianchi Stress Scale. Results. The mean participant age was 31 years; 70% of the nurses were women, 33% had more than 15 years of experience, and 88% conducted care activities. The general level of stress was medium. Stress levels were low for relationships with other units and supervisors, activities related to adequate functioning of the unit and the coordination of activities of the unit. Levels were medium for the following domains: activities related to personnel management, labor conditions for the development of nursing activities, and delivery of care to patient; this last domain was related to the following stress factors: facing patient death, attending to emergencies in the unit, advising patients' family members, and conducting tasks in the minimal time available. Conclusion. Although the general stress level was medium, the identification of domains with a high score can be used to plan intervention strategies to preserve the health of intensive care nurses and, in turn, improve quality of care delivered to severely ill patients.